Actual stress pattern and their application to structural strength estimation of tractor frame - Yadav, Ram Kumar; Koike, Masayuki; Singh, Gajendra; Gee-Clough, D.; Royal Government Belgium (Bangkok : Asian Institute of Technology, 1983)
For the design and fatigue life testing of machinery the knowledge of amplitude and frequency characteristics of stress wave is very useful. As a first step o f incorporating this technique into farm machinery design the actual stress wave of different farm operations was recorded and statistically analyzed . The PSD analysis has been found appropriate for describing the frequency characteristics of the actual stress wave. The first peak characterizes the field profile and dynamic load due to implement. The Weibull shape parameter for different field operations is found t o be in the range of 1.0 to 1.6 suggesting that, for the test conditions, the present tractor frames are overdesigned from fatigue point of view. The integrated stress pattern is obtained to furnish information on t he root mean square loads required in the random load experiments of fatigue life testing. The actual stress wave is found to follow Poisson distribution and the first asymptotic maximum probability distribution. Hence, the number and magnitude of extreme stress values can be estimated . The results provide the guidelines for carrying out further work on the topic. However, extensive work is required before this technique can be put to practical use in the design and fatigue testing of farm machinery.
A thesis submitted in partial fulfillment of the requirements for the degree of Master of Engineering, School of Environment, Resources and Development
Thesis (M.Eng.) - Asian Institute of Technology, 1983
Keywords: Tractors -- Performance